SIDIK LINTAS DALAM PENENTUAN KARAKTER SELEKSI JAGUNG TOLERAN CEKAMAN KEKERINGAN - Efendi, Roy; Aqil, Muhammad; Makalau, Andi Takdir; Azrai, Muhammad (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Information on characteristics related to drought tolerance is particularly important for improving hybrid maize yield. The present study was conducted with 62 genotypes involving tolerant, moderate, susceptible and very susceptible, for post flowering drought tolerance of hybrid maize. An experiment was conducted to determine the characteristics association between grain yield and its components and their direct and indirect effects to the yield. The research was arranged in a randomized completed block design with three replications. Drought stress treatment was started from flowering (50 days after planting, dap) until milk-dough stage (80 dap). The result indicated significant and positive association of grain yield with plant height, ear position height, stalk diameter, leaf area, leaf angle, the percentage of leaf senescence, leaves rolling score, ear length, ear diameter, number of grain/ear and shelling percentage were correlated with the yield under drought stress. Grain yield was strongly correlated with plant height, leaf area, ear length, ear diameter, and shelling percentage. Indirect effect on grain yield under drought conditions were found for the following parameters: stalk diameter, leaf angle, percentage of leaf senescence, leaf rolling scores and number of seeds/ear.